2017
DOI: 10.19082/5354
|View full text |Cite
|
Sign up to set email alerts
|

Gender differences in substance use patterns and disorders among an Iranian patient sample receiving methadone maintenance treatment

Abstract: BackgroundThe current prevalence rate of substance abuse and dependence, represents an increasing trend of substance abuse and dependence among women, and the results of epidemiology studies indicate that substance use patterns are different between men and women. This study aimed to determine gender differences in substance use patterns and disorders among the patients undergoing methadone maintenance treatment.MethodsThis cross-sectional study was conducted throughout a specified time bracket ranging from Se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 49 publications
1
12
1
Order By: Relevance
“…However, the proportion of males relative to females in our study was higher than reported in studies done in the other regions (15,16,18,21,22). This can be attributed to variation in substance use patterns in the different regions where these studies have been conducted.…”
Section: Association Of Sociodemographic Characteristics and Cannabiscontrasting
confidence: 89%
See 1 more Smart Citation
“…However, the proportion of males relative to females in our study was higher than reported in studies done in the other regions (15,16,18,21,22). This can be attributed to variation in substance use patterns in the different regions where these studies have been conducted.…”
Section: Association Of Sociodemographic Characteristics and Cannabiscontrasting
confidence: 89%
“…A systematic review of 23 studies reported prevalence of cannabis use in opioid use disorder to range 11.2%-78.6% (14). A study in Iran eported gender differenc in use where the prevalence of cannabis use in males was 25% and 5% for females (18).…”
Section: Introductionmentioning
confidence: 99%
“…Prior studies of the Farsi/Persian-translated version indicate internal consistencies ranging from .74 to .81 [17,18]. Gholami & Shareh (2015) [3] found that the scales distinguished between treatment and control groups as expected in substancedependent persons (e.g., craving and likelihood of drug use was reduced), supporting scale validity. In the current research, Cronbach's alpha was found to be 0.91.…”
Section: Measurementsmentioning
confidence: 82%
“…Women and drug abuse Given Iran's proximity to a major opioid trade route, illicit drug use is a major problem in Iran and opioids in particular are readily available [1][2][3][4]. Due to stigma, prevalence research on drug use is scant, although use of stimulants and injection drugs appears to have increased over time.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation